La vallée du Lot en Lot-et-Garonne : inventaire topographique - Alain Beschi; Hélène Mousset (In Situ)
The plan to reintroduce navigation on the Lot in the part of the river that flows through the Lot-et-Garonne department was at the origins of a survey of the heritage along the course of the river. The geographical scope of the survey was large (12 cantons along the river) and the period covered by the heritage extends from the Middle ages up to the present day. The variety of buildings to be covered required a rigorous approach and clear objectives. The method of the topographical inventory was tailored to the production of a homogenous heritage audit, based on a systematic survey of the built environment and public street furniture, without any a prioris. The first result is a catalogue presented as a database. But this rich and heterogeneous documentary corpus is not a mere collection of monographic studies. It ambition is to bring fresh light to a holistic understanding of the territory concerned. Although a synthesis of the data for the whole valley is not possible here, the examples given show how the inventory approach can bring answers and new interrogations, in particular where land occupation patterns are concerned and the relations between architecture and landscape. The inventory of this vast rural territory therefore hopes to bring information at three levels of analysis: the research of heritage traces for a particular period, the long-term permanence of the build environment and the observation of the traces of historical change and mutation.